The great nerve : the new science of the vagus nerve and how to harness its healing reflexes - Tracey, Kevin J. (Avery, an imprint of Penguin Random House, 2025)
The vagus nerve is fundamental to our health and vitality, coordinating critical functions from the precise heartbeat we need to exercise or rest to the balance of appetite and digestion. Made up of 200,000 fibers, the vagus nerve sends thousands of electrical signals every second between your brain and your most important organs. Yet despite its essential role in life, important vagus nerve functions have eluded centuries of scientific investigation. Now neurosurgeon and researcher Kevin Tracey has discovered the previously unknown power of the vagus nerve to reverse inflammation, balance the immune system, treat chronic illness, and keep our organs humming together in harmony. In The Great Nerve, Dr. Tracey shows us how stimulating the vagus nerve with a tiny electrical implant has the potential to reverse life-altering diseases like rheumatoid arthritis, inflammatory bowel disease, lupus, MS, diabetes, obesity, stroke, depression, Alzheimer's and Parkinson's. If this sounds too good to believe, Dr. Tracey shares stories of patients who have gone from being nearly bedridden to running and dancing, along with the science that makes possible these recoveries. He also explains the evidence for lifestyle strategies like ice baths, meditation, exercise, and breathwork that can maintain and improve vagus nerve function. By opening the door to the new field of neuroimmunology, The Great Nerve not only revolutionizes how we understand and treat disease, it gives us unprecedented hope for our health. This is the story of your body's ability to heal itself.